DC-SIGN Binding Contributed by an Extra N-Linked Glycosylation on Japanese Encephalitis Virus Envelope Protein Reduces the Ability of Viral Brain Invasion - Liang, Jian-Jong; Chou, Min-Wei; Lin, Yi-Ling (Frontiers in Cellular and Infection Microbiology, 2018)
The major structural envelope (E) protein of Japanese encephalitis virus (JEV) facilitates cellular binding/entry and is the primary target of neutralizing antibodies. JEV E protein has one N-linked glycosylation site at N154 (G2 site), but the related dengue virus E protein has two glycosylation sites at N67 (G1 site) and N153 (G2 site). We generated three recombinant JEVs with different glycosylation patterns on the E protein. As compared with wild-type (WT) JEV with G2 glycosylation, viral growth in culture cells as well as neurovirulence and neuroinvasiveness in challenged mice were reduced when infected with the G1 mutant (E-D67N/N154A) with glycosylation shifted to G1 site, and the G0 mutant (E-N154A) with non-glycosylation. The G1G2 mutant (E-D67N), with E-glycosylation on both G1 and G2 sites, showed potent in vitro viral replication and in vivo neurovirulence, but reduced neuroinvasiveness. Furthermore, the JEV mutants with G1 glycosylation showed enhanced DC-SIGN binding, which may then lead to reduced brain invasion and explain the reason why WT JEV is devoid of this G1 site of glycosylation. Overall, the patterns of N-linked glycosylation on JEV E proteins may affect viral interaction with cellular lectins and contribute to viral replication and pathogenesis.